Assessing the Potential of Social Innovation and Local Agenda-Setting within Rural Development Programmes: Insights from Austrian Leader Regions - Sune Wiingaard Stoustrup (European Countryside, 2022)
Since the beginning of the 1990s, the LEADER programme has been implemented to promote positive development in rural areas in the EU through bottom-up approaches and community engagement. Lately, concerns have been raised about the capability of LEADER to foster social innovation and provide adequate room to manoeuvre for communities to set agendas locally. This paper attempts to engage in this discussion by analysing the implementation of rural development programmes, local ideas and experiences with LEADER and social innovation in four LEADER regions in Upper Austria (AT). Furthermore, the analysis outlines the projects implemented through LEADER to evaluate the possibilities for local agenda-setting. The research shows both the success of LEADER as a tool to instigate bottom-up and neoendogenous development and the need for additional institutional frameworks for community consultations if inclusive and forward-looking visions of rural development are to be fostered.
Keywords: 320; Austria; LEADER programme; neo-endogenous rural development; social innovation